A new species of Homatula from the Red River drainage in Yunnan based on morphological and genetic data (Teleostei: Nemacheilidae) - Endruweit, Marco; Min, Rui; Yang, Junxing (Zootaxa, 2018)
Homatula coccinocola, new species, is described from a Red River affluent in Honghe Prefecture, Yunnan, China. The combination of a fully scaled body, a notched lower jaw, 4+42–44 vertebrae, 11 pectoral-fin and 8 pelvic-fin rays, and a color pattern of 16–19 brown, somewhat straight and vertically solid bars on a beige background distinguishes the new species from its congeners. The generic diagnosis of Homatula is revised.